Recent judicial devlopments in the field of administrative contract disputes and their impact on the theory of separate administrative decisions an analytical study - Ibrahim, Researcher: Avan Khalil Ibrahim; Hussein, Prof.Dr. Mustafa Rasool Hussein (Sulaimani Journal for Humanities, 2025)
This study addresses the shortcomings and deficiencies in the theoretical structure of the theory of severable administrative decisions, as well as the practical issues surrounding its application. It highlights the impact of recent judicial developments on this theory and attempts to identify areas of expansion regarding the extent to which certain pre-contractual stages can be subject to appeal. The research also explores the practical challenges in this phase and seeks to establish an effective safeguard for appealing such decisions. This is approached through a methodological vision that supports the appealability of certain pre-contractual decisions, even if they do not fall strictly under the theory of separable administrative acts, especiall